Some results of studying laser micromachining at medical stents manufacturing. (23rd August 2010) - Kovalenko, V.; Anyakin, M.; Zhuk, R.; Kondrashev, P.; Stepura, O.; Meijer, J.
Cardio-vascular diseases are the number one killer in the world. As an alternative to common treatment methods the installation of specific-purpose stents into the damaged blood vessel could be used in order to minimise fatal outcomes. Existing technologies of stent manufacturing provide quite good results but are very expensive at the moment. The given paper deals with the design of stents for cardio-vascular surgery and their manufacturing with help of Q-switched Nd-YAG laser which is considered to be much cheaper and more efficient. The methods of nonlinear programming together with methods of experiments planning were used to find the optimal processing conditions and create adequate numerical models of the process. Several processing schemes based on direct laser cutting and step-by-step laser milling had been considered in the research. Some processing dependencies had been established as well as the possibility to create the special micro-relief on the machined surface with help of laser milling. It was demonstrated that due to the assist gas stream action the micro deformation of the stent's workpiece occurs thus influencing the final machining quality.